Hypnotic Modulation of Autonomic Nervous System (ANS) Activity - Giuseppe De Benedittis (Brain Sciences, 2024)
Hypnosis, a time-honored therapeutic approach, has gained widespread recognition for its effectiveness in addressing a range of psychological and somatic disorders. While its primary effects are mediated by central top–down mechanisms, hypnosis also exerts peripheral influence by modulating the autonomic nervous system (ANS). Psychophysiological measures, such as heart rate (HR) and its variability (HRV), electrodermal activity (EDA), respiratory rate (RR), and the analgesia nociceptive index (ANI), serve as reliable indicators of ANS activity. Studies have consistently demonstrated hypnosis’ ability to significantly impact ANS functions, lowering sympathetic activity and enhancing parasympathetic tone. This effect is particularly pronounced during relaxation procedures and is influenced by mediating factors like hypnotizability and task conditions. Despite methodological limitations, this review highlights the potential of enhanced ANS modulation through hypnosis, including its connections to the central nervous system (CNS), to optimize therapeutic outcomes in patients with psychosomatic disorders associated with ANS dysfunction.